El poder moral de la razón : la filosofía de Gramsci / Ramón Vargas-Machuca Ortega ; prólogo de Miguel A. Quintanilla - Quintanilla, Miguel A.; Vargas-Machuca Ortega, Ramón (Serie de Filosofía y Ensayo)
Bibliografía: p. 227-235